2021
DOI: 10.3390/ijerph182211978
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Township Hospitals Health Workers on How They Are Paid in China

Abstract: Background: Township Hospitals (THs) are crucial providers in China’s primary health delivery system. Low job satisfaction of THs health workers has been one of biggest challenges to strengthening the health system in China. Even huge amounts of studies confirmed low remuneration level as a key demotivating factor though few studies have explored the feelings of health workers on how they were paid. Objective: To analyze how the key design of Performance-based Salary System (PBS) influences the satisfaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Because this hospital is a private hospital, not government-owned. This finding is quite confusing because it contradicts the theory that salary is a driving force for enthusiasm to work to improve performance [20], [21]. Salary is remuneration provided by the agency to workers [22].…”
Section: Discussionmentioning
confidence: 93%
“…Because this hospital is a private hospital, not government-owned. This finding is quite confusing because it contradicts the theory that salary is a driving force for enthusiasm to work to improve performance [20], [21]. Salary is remuneration provided by the agency to workers [22].…”
Section: Discussionmentioning
confidence: 93%
“… 20 , 41 One reason might be that the culture of the workplace PHCIs are strongly influenced by traditional Chinese culture, which is that the doctrine of the equal income distribution and preference for stability. 42 Therefore, most PCPs may prefer stable income rather than higher percentage of income being floated based on their job performance. Another reason is that the performance-based salary system has not designed and developed very well.…”
Section: Discussionmentioning
confidence: 99%
“…Then, they adopted a gray relational analysis (GRA) and gray prediction model to calculate the weight of effective salary criteria, players’ annual performance index, and next year’s salary forecast. Yuan et al ( 2021 ) found that the satisfaction level of health workers is related to their monetary income. Chang et al ( 2021 ) examined that the service motivation theory is valid for doctors’ job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%